2007
DOI: 10.3758/bf03193047
|View full text |Cite
|
Sign up to set email alerts
|

Temporal generalization and peak shift in humans

Abstract: Three experiments investigated temporal generalization in humans. In Experiment 1, a peak shift effect was produced when participants were given intradimensional discrimination training. In Experiment 2, after training with a standard S and generalization testing with an asymmetrical series of durations, generalization gradients moved toward the prevailing adaptation level. In Experiment 3, generalization gradients showed a central tendency shift and moved away from the S and toward the mean of the test series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Bizo and McMahon (2007) recently reported that individuals trained to discriminate squares presented for different durations (e.g., 0.79 s versus 0.95 s) showed a peak shift effect along the dimension of duration. Russell and Kirkpatrick (2005) acquired similar results with rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bizo and McMahon (2007) recently reported that individuals trained to discriminate squares presented for different durations (e.g., 0.79 s versus 0.95 s) showed a peak shift effect along the dimension of duration. Russell and Kirkpatrick (2005) acquired similar results with rats.…”
Section: Discussionmentioning
confidence: 99%
“…In a classic example, pigeons trained on a wavelength discrimination between 550 nm light (S+) and 560 nm light (S−) responded most to shorter wavelengths such as 540 nm in a generalization test (Hanson, 1959). Such learning-related gradient shifts have been observed in bees (Lynn, Cnaani, & Papaj, 2005), horses (Dougherty & Lewis, 1991), rats, goldfish, guinea pigs, chickens, pigeons, and humans (reviewed by Purtle, 1973), and with various methods such as category learning (McLaren, Bennett, Guttman-Nahir, Kim, & Mackintosh, 1995; McLaren & Mackintosh, 2002; Wills & Mackintosh, 1998), varying distributions of test stimuli (Bizo & McMahon, 2007; Helson & Avant, 1967; Spetch, Cheng, & Clifford, 2004; Thomas & Bistey, 1964), and training with multiple S+ stimuli (Galizio & Baron, 1979; White & Thomas, 1979). The effect occurs for stimuli varying in brightness (Newlin et al, 1979; Thomas, Ost, & Thomas, 1960; White & Thomas, 1979; Thomas, Mood, Morrison.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptation-level theory has been applied to explaining temporal judgments, predominantly within prospective paradigms (e. g., [19,20,21]). However, the main principle of adaptation-level theory, namely that judgments of stimuli (durations) are affected by a frame of reference, is valid for both judgment paradigms.…”
Section: Introductionmentioning
confidence: 99%